INSTRUCTIONAL STRATEGIES OF ISLAMIC EDUCATION TEACHERS IN TEACHING ISLAMIC CULTURAL HISTORY (SKI) AT MI MATHLAUL HUDA RANCAGONG - Rizki, Reffy Ananda; Mujiburrohman, Mujiburrohman; Aniyatussaidah, Aniyatussaidah; Syairoh, Anna Navita; Mulyanih, Sri (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2025)
Islamic Cultural History (Sejarah Kebudayaan Islam/SKI) is a fundamental subject within the Islamic Religious Education curriculum at the Madrasah Ibtidaiyah (MI) level, yet it is frequently perceived by students as monotonous and difficult due to its heavy emphasis on memorization and limited pedagogical variety. This study aims to examine the instructional strategies employed by Islamic Education teachers at MI Mathla’ul Huda Rancagong, with a particular focus on the application of mind mapping and timeline techniques. Utilizing a qualitative descriptive methodology, data were collected through interviews, classroom observations, and document analysis involving purposively selected participants. The findings indicate that mind mapping facilitates visual organization of complex historical concepts, improves memory retention, and promotes critical thinking, creativity, and student engagement. Meanwhile, the use of timelines enhances students’ chronological thinking and their ability to comprehend historical sequences and causal relationships. These strategies are consistent with both constructivist and humanistic learning theories, positioning students as active participants in the learning process. The integration of visual-based instructional tools not only improves students’ academic outcomes but also fosters more meaningful and engaging learning experiences. This study contributes to pedagogical innovation in Islamic education by offering practical recommendations for educators, school administrators, and policymakers. It also suggests avenues for future research focusing on the integration of multiple visual learning strategies, application across different educational levels, and exploration in diverse sociocultural contexts